Staging the savage god - Remshardt, Ralf (Southern Illinois University Press, 2004)
Cover; Title Page; Copyright; Dedication; Contents; List of Figures; Acknowledgments; Introduction: Approaching the Grotesque; 1. The Sense of Disorder; 2. Theories; 3. Classical Grotesque; 4. Kunstfiguren; Conclusion: The Paradoxes ofa Grotesque Theatre; Notes; Bibliography; Index; About the Author; Back Cover
Includes bibliographical references (pages 275-289) and index
Keywords: Electronic books; Drama; Grotesque in literature